Gelatin Properties of Goat Skin Produced by Calcium Hydroxide as Curing Material - M. I. Said; S. Triatmojo; Y. Erwanto; A. Fudholi (Media Peternakan, 2011)
Application of strong bases as curing materials has been widely applied in commercial gelatin industries, but the application of weak bases has not been much done. Application of strong bases as a treatment was not economical and assumed to affect human health. Studies were conducted on the properties of goat skin gelatin manufactured using weak base types of Ca(OH)2 and then compared with properties of commercial gelatin. Skins from Bligon goats of 1.5 to 2.5 years old was used as the raw materials and Ca(OH)2 100 g/l as curing materials. The 2x3 factorial completely randomized design (CRD) with three replications was used as a design study. Two curing times (2 and 4 days) and three concentrations (3, 6, 9% v/v) were used as treatments, and commercial gelatin (pure (P) by Merck, food grade (Fg) and pharmacy standards (Ps)) were used as control. Gelatin produced from goat skins using Ca(OH)2 had properties similar to that of commercial gelatin. The heavy metals (Pb, Cu and Zn) contained in goat skin gelatin still meet the INS standards. The optimum production of gelatin has been generated through the application of 4-day curing time at a concentration of 9% (v/v).